2020
DOI: 10.4162/nrp.2020.14.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of infections in schoolchildren subsequent to supplementation with vitamin D-calcium or zinc: a randomized, double-blind, placebo-controlled trial

Abstract: BACKGROUND/OBJECTIVES: Vitamin D and zinc are recognized for their roles in immune-modulation, and their deficiencies are suggested to be important risk factors for childhood infections. This study, therefore, undertook to assess the occurrence of infections in rural Indian schoolchildren, subsequent to daily supplementation with vitamin D-calcium or zinc for 6 months. SUBJECTS/METHODS: This was a randomized, double-blind, placebo-controlled trial in apparently healthy 6-12 year-old rural Indian children, recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It acts as a negative regulator of the signaling pathways of NF-kB [56] and interferon [57], i.e., it suppresses the production of inflammatory cytokines and modulates the response to viral infections. The latter is a long overlooked effect of vitamin D on the immune system [58,59] and a reason why vitamin D deficiency may lead to high vulnerability against viral infections in the elderly, but also in school children [15,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a negative regulator of the signaling pathways of NF-kB [56] and interferon [57], i.e., it suppresses the production of inflammatory cytokines and modulates the response to viral infections. The latter is a long overlooked effect of vitamin D on the immune system [58,59] and a reason why vitamin D deficiency may lead to high vulnerability against viral infections in the elderly, but also in school children [15,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…From the early 2000s, various studies were conducted, mainly in children from lower socio-economic settings, to establish whether daily or weekly zinc supplementation could help in preventing respiratory tract infections ( Table 9 ) [ 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 ].…”
Section: Zincmentioning
confidence: 99%
“…In 2007, Sazawal et al reported a slight reduction in the relative risk of all-cause mortality in children supplemented with zinc in Zanzibar [ 277 ]. Other studies found instead that zinc supplementation had no significant effect on the frequency of respiratory infections [ 274 , 275 , 276 , 278 , 279 , 281 ]. Some of these trials used a lower daily dose of zinc, which might be one of the reasons why the supplementation was less effective; however, both negative and positive results were reported with different zinc dosages, from 5 up to 30 mg/day.…”
Section: Zincmentioning
confidence: 99%
“…30 Since the date of the final literature search in this previous meta-analysis (Dec 31, 2015), 21 RCTs involving 64 220 participants who fulfilled the same eligibility criteria have been done (including four with unpublished data [NCT02404623, NCT02046577, NCT01875757, and NCT01758081]). [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] We therefore sought data from these more recent studies for inclusion in an updated metaanalysis of stratified aggregate (ie, trial-level) data to establish whether vitamin D supple mentation reduced overall ARI risk, and to evaluate whether the effects of vitamin D supplementation on ARI risk varied according to baseline 25(OH)D concentration, dosing regimen (frequency, dose, and trial duration), or age at enrolment.…”
Section: Introductionmentioning
confidence: 99%